1969
DOI: 10.2134/agronj1969.00021962006100040001x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Coated Urea and Uncoated Soluble Nitrogen Fertilizers for Fescue Forage1

Abstract: Field experiments were carried out during 1965–67 to compare rates, sources and times of N topdressing for ‘Kentucky 31’ fescue (Festuca arundinacea). Uncoated ammonium nitrate (AN), urea, and other readily soluble N fertilizers resulted in higher first‐cutting yields, which were higher in content of total N. Sulfur‐coated urea (SCU) resulted in lower first‐cutting and higher later‐cutting yields than did the soluble N sources. Total annual yields were usually similar with all N sources. Mixtures of AN and SCU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1973
1973
1992
1992

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…The total N uptake by fescue treated with N plus P fertilizer was similar to N uptake resulting from compost applied at a rate of 6%. Comparing efficiencies of N uptake by the plant from N plus P fertilizer and compost, fescue absorbed about 76% of the applied N fertilizer (comparable to that observed by Mays and Terman, 1969; and Eck et a!., 1981) while fescue grown on compost amended soils absorbed about 8% of the total N added in compost (comparable to the observations by Amberger et a!., 1980). It appears then that fescue utilization of compost N is approximately 10% of that for NH 4 N0 3 in this greenhouse experiment.…”
Section: Resultssupporting
confidence: 82%
“…The total N uptake by fescue treated with N plus P fertilizer was similar to N uptake resulting from compost applied at a rate of 6%. Comparing efficiencies of N uptake by the plant from N plus P fertilizer and compost, fescue absorbed about 76% of the applied N fertilizer (comparable to that observed by Mays and Terman, 1969; and Eck et a!., 1981) while fescue grown on compost amended soils absorbed about 8% of the total N added in compost (comparable to the observations by Amberger et a!., 1980). It appears then that fescue utilization of compost N is approximately 10% of that for NH 4 N0 3 in this greenhouse experiment.…”
Section: Resultssupporting
confidence: 82%
“…A unique characteristic of SCU that could limit its utility was a very uniform pattern of spotted response of ryegrass (overseeded on bennudagrass) maintained at threefourths inch or less. Latent pellet counts in high response spots vs. low response spots indicated that a significant fraction of the round SCU pellets was 7 Mazur, A. R., and T. D. Hughes. 1973.…”
Section: Resultsmentioning
confidence: 99%
“…The material consists of urea granules with various coatings (usually S), a sealant, a microbicide, and a conditioner (Rindt et al, 1968). Several investigations have demonstrated the slow release characteristic of SCU and its agronomic advantages over more soluble N sources for production of several crops (Mays and Terman, 1969;Allen and Mays, 1971;Dalal, 1974;Gascho and Snyder, 1976). The purpose of this study was to examine the agronomic efficiency of fall-applied SCU, uncoated urea, and NaN0 3 compared to spring preplant applications for corn and to make yield comparisons among the sources.…”
mentioning
confidence: 99%